Consumer Digital Trust: The Influence of Online Ratings and Reviews on Purchasing Decisions for Glad2Glow Skincare Products on Shopee - Putri Maylani Sihnap; Citra Savitri; Syifa Pramudita Faddila (STIE Amkop Makassar, 2026)
This study aims to examine the impact of ratings and reviews on the purchase decisions of Glad2Glow skincare products through the Shopee platform by Generation Z in Karawang. The research method used in this study was a quantitative approach. The sample used in this study was 96 respondents. The data analysis used in this study was multiple linear regression analysis. The research findings revealed that ratings and reviews have a positive and meaningful influence on purchasing decisions, both individually and together. Ratings showed a stronger dominance than reviews. The coefficient of determination of 0.426 indicates that 42.6% of the variation in purchasing decisions can be explained by ratings and reviews.The conclusion shows that ratings and reviews are key elements influencing the purchasing choices of Generation Z consumers on the Shopee platform, with ratings being the factor with the greatest influence. This research offers practical benefits for skincare entrepreneurs in designing digital marketing strategies, particularly through the use of ratings and reviews to encourage purchasing decisions among Generation Z consumers.